Mengidentifikasi Jati Diri Cipta untuk Membangun Karakter Mahasiswa Agar Mencapai Kesuksesan di Masa Depan - Shiva Nabila; Edy Soesanto; Muhammad Areevo Al Islami Putra (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
In the era of globalization that is full of challenges, the ability to think critically is becoming increasingly relevant. This research aims to examine how the integration of the trilogy of soul aspects (rasa, cipta, and karsa) in the learning process can foster critical thinking character in the younger generation. Through literature review and case studies, this research will identify learning strategies that are effective in stimulating students' critical thinking skills, as well as analyze their influence on overall character development. The results of the research are expected to contribute to the development of a more holistic curriculum and teaching practices, so as to produce a young generation that is not only intellectually intelligent, but also has a strong and competitive character. The formation of critical thinking character does not only involve the teaching and learning process in the classroom, but also needs to be balanced with real experiences outside the academic environment. Through a holistic approach, it is hoped that the younger generation will be able to develop critical thinking skills that are not only useful in the context of education, but also in everyday life. Education based on this trilogy of aspects of the soul will provide a strong foundation for young people to face global challenges and contribute positively to society. This trilogy includes intellectual understanding, emotional and values development, and practical skills that support each other. By integrating these three aspects, education will not only shape individuals who are intellectually intelligent, but also have social awareness and adaptability in a changing society. Character education has become a central issue in education today. This research proposes that integrating the trilogy of aspects of the soul can be an effective approach in building critical thinking character in the younger generation. By stimulating the trilogy aspects in a balanced manner, it is expected that they will be able to develop critical thinking skills that are not only logic-based, but also based on moral values and empathy. This research will test this hypothesis through experiments or case studies at an educational institution.